Upaya Meningkatkan Hasil Belajar Siswa melalui Model Pembelajaran Discovery Learning pada Mata Pelajaran IPA Kelas VII di SMP Negeri 10 Padang - Sari, Ayu Puspita; Putri, Rahma Evita; Yenira, Fitria (TSAQOFAH, 2025)
The low academic achievement of students in science subjects at SMP Negeri 10 Padang is attributed to limited conceptual understanding, low enthusiasm for the material, a lack of relevance between lessons and daily life, and the predominance of one-way teacher communication. This study aims to improve student learning outcomes through the implementation of the discovery learning model among Class VII.3 students, consisting of 32 participants. The research employed a Classroom Action Research (Penelitian Tindakan Kelas) design conducted over two cycles. Data were collected through multiple-choice tests and analyzed quantitatively to assess improvements in learning outcomes. The results showed that the average pre-cycle score was 69.56 with a mastery level of 53.13%. In the first cycle, the average increased to 77.59 with 68.75% mastery, and in the second cycle, it further improved to 86.25 with 84.38% mastery. These findings demonstrate that the application of discovery learning is effective in enhancing science learning outcomes. Learning activities that emphasize student exploration strengthen conceptual understanding, enhance memory retention, and promote critical thinking skills. Therefore, discovery learning is a relevant student-centered approach for improving the quality of science learning outcomes at the junior high school level.